Isolasi Asam Humat Dan Aplikasinya Sebagai Sensitizer Dalam Fotoreduksi Fe(III) = Isolation of Humic Acids and Its Application as Sensitizer on the Photoreduction of Fe(III) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT A study on the isolation of humic acids from peat soil which is taken from Sambutan village of Samarinda Ilir subdistrict, in Samarinda regency of East Kalimantan and its application as sensitizer in the photoreduction of the Fe(III) to Fe(II) has been conducted. The influencing parameters on the reduction and photoreduction efficiencies that consisted of : medium acidity, radiation duration, the initial concentration of humic acids and Fe(III) were optimized. The study was begun with the optimazation of the determination of the Fe(II) with 1,10-phenanthroline complexing agent using UV-visible spectrophotometer, as well as isolation, purification and characterization of humic acids from the peat soil sample. The efficiency of the photoreduction of Fe(I/I) in the presence and absence of humic acids was determined using the difference between the reduced Fe(III) in a solution before and after radiation. The result of study showed that the optimum condition for Fe(II) analysis with 1,10-phertanthrohne as complexing agent using UV-visible spectrophotometer was at X. 510 nm, pH 4, stability time at 10 min after the addition of the complexing agent and minimum 1,10-phenanthroline Fe(II) mol ratio of 3:1. Under this optimum condition, sensitivity of 0.19 mg/L and the detection limit of 0.03 mg/L were obtained. At pH 4 and the humic acids concentration of .50 mg/L, 5 mg/L of Fe(III) was completely reduced after 180 minutes of radiation.lt was revealed from the study that the -OH groups of humic acids were playing the dominant role as donor electron in the Fe(III) photoreduction. The trapping of -OH groups of humic acids with 2- propanol only resulted photoreduction of Fe(III) as high as 21.36 % or 1.07 mg/L of the total Fe(III) 5 mg/L.